Mapping of scientific research on ecotoxicological analysis with zebrafish (Danio rerio) in textile effluents between 2011 and 2021 - Raíza Alves Cavalcante , Paula; Cândido Passos da Silva , Rodrigo; Gonçalves Cadena , Pabyton; Gomes Tavares, Rosângela (Periódico Eletrônico Fórum Ambiental da Alta Paulista, 2023)
The high load of pollutants in textile industrial effluents makes it necessary to carry out an ecotoxicological analysis. Mapping these analyses in animal models can help clarify the possible toxicity that these textile effluents have. Thus, the present study aimed to map the evolution of scientific publications regarding the use of zebrafish (Danio rerio) as a bioindicator animal model for environmental quality analysis in the ecotoxicological analysis of textile effluents over a ten-year horizon (2011 to 2021). Three methodological steps were established: a sampling of articles, scientometric and bibliometric analyses, and a systematic literature review. It was observed in twelve documents that ecotoxicological studies of textile effluents using zebrafish are a recent and understudied but promising trend. Among the works, those originating from the Asian continent stood out. The Environmental Science and Pollution Research journal had only two publications. The similarity analysis generated a word tree with seven groups (halos). It was understood that industrial textile effluents have a direct connection with toxicity caused by dyes, and this toxicity can be detected by analysis carried out with the zebrafish bioindicator. It was observed that ecotoxicological assessments with zebrafish could be carried out through different methodologies. However, some proved more complex and presented more robust results, such as embryonic and larval analyses. These analyses were considered beneficial compared to other animal models because they are low cost, require a short period, and comply with an internationally imposed standard (OECD 236). Therefore, it concluded that zebrafish is a promising model for ecotoxicological analysis of textile effluents.